Anti-inflammatory agents and substance P depletion in experimental ileitis - M. J. S. Miller; H. Sadowska-Krowicka; S. Chotinaruemol; M. Wong; D. A. Clark; A. Y. Jeng (Hindawi Limited, 1993)
To understand the interactions between substance P and gut inflammation, changes in substance P levels were evaluated in a chronic model of ileitis in response to three anti-inflammatory agents with distinct mechanisms of action. The agents were the prostaglandin E1 analogue misoprostol (30 μg/kg, s.c., b.i.d.), the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME, 100 μg/ml in drinking water) and the leumedin, N-(fluorenyl-9-methoxycarbonyl)-L-leucine (NPC 15199, 10 mg/kg, s.c.). Ileitis was induced by a transmural injection of trinitrobenzene sulphonic acid (TNBS 30 mg/kg in 50% ethanol) into the distal ileum of guinea-pigs. All anti-inflammatory therapies were introduced after TNBS administration and continued until day 7, when guinea-pigs were killed. Ileal substance P levels were measured by radioimmunoassay, and granulocyte infiltration was quantified by myeloperoxidase (MPO) activity. Protein and nitrite (an index of nitric oxide formation) levels in a luminal saline lavage were quantified in all groups. TNBS ileitis caused a marked reduction in ileal substance P content and increased MPO activity, protein and nitrite secretion. The nitric oxide synthase inhibitor, L-NAME, completely restored all parameters to baseline. Misoprostol attenuated the granulocyte infiltration and exacerbated protein leak but had no effect on substance P levels. In contrast, NPC 15199 had no effect on granulocyte infiltration but normalized substance P levels and protein leak. Only L-NAME and NPC 15199 blocked the TNBS induced increase in nitrite levels. These results suggest that the regulation of granulocyte infiltration in this model is unrelated to changes in substance P levels. Inhibition of nitric oxide synthase was the most effective therapeutic strategy in TNBS ileitis but the precise interactions between nitric oxide and the enteric nervous system during inflammatory states remain to be defined.